Stuck on you [videorecording (DVD)] - Farrelly, Bobby, 1958-; Farrelly, Peter; Damon, Matt; Kinnear, Greg, 1963- (Twentieth Century Fox Home Entertainment, 2004)
Conjoined twins, Bob and Walt, are happy living their lives together and manage just fine, playing hockey, working at the diner, and cruising for babes, until one decides he wants to be an actor and the other has stage fright and panic attacks.